This Murder Done : Misogyny, Femicide, and Modernity in 19th-Century Appalachian Murder Ballads - Hastie, Christina Ruth (2011)
This thesis contextualizes Appalachian murder ballads of the 19th- and early 20th-centuries through a close reading of the lyric texts. Using a research frame that draws from the musicological and feminist concepts of Diana Russell, Susan McClary, Norm Cohen, and Christopher Small, I reveal 19th-century Appalachia as a patriarchal, modern, and highly codified society despite its popularized image as a culturally isolated and “backward” place. I use the ballads to demonstrate how music serves the greater cultural purpose of preserving and perpetuating social ideologies. Specifically, the murder ballads reveal layers of meaning regarding hegemonic masculinities prevalent in 19th-century and turn-of-the-20th-century Appalachian culture. This work also explores the biases and agendas of the early folksong projects in the United States. Examining the arguments of early scholars, I consider the American tradition in juxtaposition to the earlier British forms of music. Rejecting earlier scholarship that argues for the relatedness of British and American balladry, I find that ballads associated with, and circulating in, the United States instead reflect a new cultural idiom grounded in the beliefs of those who sought a conservative Christian aesthetic and way of life in the southern Appalachian mountains. The murder ballads witness that Appalachia, specifically in the 19th-century period of industrial change, was defined by essential tensions between cultural traditions of the past and emerging notions of American modernism. This tension is met in the songs with responses of violence against women whose life situations—marked by sexual freedom—are the very depiction of a new cultural modernism that threatens the hegemony of the past